2022
DOI: 10.3390/ijerph19063383
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain and Work Conditions of Hotel Housekeepers: A Descriptive Study

Abstract: Objectives: To estimate the prevalence of musculoskeletal pain of hotel housekeepers (HHs) and to describe the work conditions and perception of health in this occupational group in the Balearic Islands, Spain. Methods: Cross-sectional descriptive study with HHs of the Balearic Islands, performed in primary care. Random sample of HHs who worked during the 2018 season. We collected information on sociodemographic variables, job characteristics, workload, pain, perceived health, and physical activity. After part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These characteristics seem to reflect the gender and low social positions of housekeeping managers. Although many studies have reported on hotel housekeeping managers [ 12 , 33 ], platform-based housekeeping managers, as examined in this study, were required to visit not only hotels but also any location requested by customers through the platform, which is a different concept from previous studies. Housekeeping managers in platform-based occupations are likely to engage in much more atypical labor as their workplace varies, exposing them to various types of violence due to the absence of employers to ensure their safety.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics seem to reflect the gender and low social positions of housekeeping managers. Although many studies have reported on hotel housekeeping managers [ 12 , 33 ], platform-based housekeeping managers, as examined in this study, were required to visit not only hotels but also any location requested by customers through the platform, which is a different concept from previous studies. Housekeeping managers in platform-based occupations are likely to engage in much more atypical labor as their workplace varies, exposing them to various types of violence due to the absence of employers to ensure their safety.…”
Section: Discussionmentioning
confidence: 99%
“…Mattresses which are heavy increase the occurrence of pain in some body parts. Sánchez-Rodríguez et al (2022) focused their study on 'Chronic pain and work conditions of hotel housekeepers' highlighted that pain was related with age, experience, pushing of the trolley and bed making. Joshi (2016) focused in their research on the 'Study of Relationship Between Ergonomics & Efficiency of the Housekeeping Employees at Workplace' that housekeeping work involves routine and repetitive work which easily leads to occupational injuries which have direct impact on the productivity of the staff.…”
Section: Introductionmentioning
confidence: 99%